The Effect of Employer Branding, Employee Branding and Job Satisfaction and Engagement as Mediation Variables on the Performance of Nurses in A Hospital Type E - Windayanti Windayanti; Wibowo Wibowo; Hamidah Hamidah; Widarto Rachbini (Budapest International Research and Critics University, 2022)
This study aims to test, review and analyze in order to know, a picture of the influence of employer branding, employee branding, job satisfaction, and engagement as a mediating variable on the performance of hospital nurses type E. The study was conducted with a survey method against three hundred and fifty respondents using a questionnaire. While testing and data analysis were done using the technique of the analysis of Structural Equation Models (SEM) through the program SMART PLS Version 3.0. The results of the research show that Employer branding has a strong influence and positive impact on employee engagement. Employee branding influences the medium and positive impact on employee engagement. Job satisfaction influences the medium and positive impact on employee engagement. Employer branding influences the medium and positive impact on performance. Employee branding influences a weak and positive impact on performance. Job satisfaction has an influence is a weak and positive impact on performance. Engagement mediates the influence of employer branding on performance. Employee engagement mediates the influence of employee branding on performance. Employee engagement mediates the effect of job satisfaction on performance. Thus, engagement is proven to mediate the reinforcement influence on the performance of nurses in a hospital type E.